Production of prosodic cues in coordinate name sequences addressing varying interlocutors. Issue 1 (25th January 2021) - Huttenlauch, Clara; de Beer, Carola; Hanne, Sandra; Wartenburger, Isabell
Prosodic boundaries can be used to disambiguate the syntactic structure of coordinated name sequences ( coordinates ). To answer the question whether disambiguating prosody is produced in a situationally dependent or independent manner and to contribute to our understanding of the nature of the prosody-syntax link, we systematically explored variability in the prosody of boundary productions of coordinates evoked by different contextual settings in a referential communication task. Our analysis focused on prosodic boundaries produced to distinguish sequences with different syntactic structures (i.e., with or without internal grouping of the constituents). In German, these prosodic boundaries are indicated by three major prosodic cues: f0-range, final lengthening, and pause. In line with the Proximity/Anti-Proximity principle of the syntax-prosody model by Kentner and Féry (2013 ), speakers clearly use all three cues for constituent grouping and prosodically mark groups within and at their right boundary, indicating that prosodic phrasing is not a local phenomenon. Intra-individually, we found a rather stable prosodic pattern across contexts. However, inter-individually speakers differed from each other with respect to the prosodic cue combinations that they (consistently) used to mark the boundaries. Overall, our data speak in favour of a close link between syntax and prosody and for situational independence of disambiguating prosody.